Modeling the relations of motivational variables as explanatory factors of science achievement in Malaysian context / Wong Su Lee - Wong, Su Lee (2018)
Adapting a combination of theory of epistemological beliefs, achievement goal theories, implicit theories of intelligence and theory of self-efficacy, this study examined the role of epistemological beliefs and implicit theories of intelligence in relation to students’ achievement in science , mediated by achievement goals, self-efficacy and learning approach. A quantitative correlation study was designed to relate and model these factors for science achievement. The samples for the present study were 350 form four students from selected districts in Pahang, Malaysia. By using adapted questionnaires, data was collected and analyzed using SPSS and Smart PLS software. The analysis of the direct paths revealed that epistemological beliefs, self-efficacy, implicit theories of intelligence, learning approaches and goal orientation strongly affected students’ achievement in science. In the second phase of the study, mediation roles were identified and the findings revealed that epistemological beliefs strongly effected science achievement via mastery performance, but the effect of avoidance goal was non-significant and negative. While considering the mediation effect of self-efficacy, results revealed that self-efficacy played partial mediation role with respect to epistemological beliefs, but no such effect was observed from implicit theories of intelligence. In learning approach, deep approach only played a partial mediation role with respect to epistemological beliefs, implicit of intelligence, performance goals and self-efficacy while surface approach played a partial mediation role to avoidance goal only. On the whole, it can be concluded that epistemological beliefs, goal orientations (both mastery and performance goals) and deep approach can be effectively employed to boost the students’ science achievement and to ensure that teaching and learning of science may become more effective and excellent.